The social determinants of health in empowering patient education intervention studies : Integrative literature review - Poraharju, Jenna (My University, 2024)
Background: The social determinants of health (SDOH) are central part of strategic plans to achieve health equity and sustainable development goals. SDOH are the non-medical factors that influences health outcomes. They are conditions that people born, live and work, including various socioeconomic and environmental conditions influencing on individuals’ health. Previous research tends to emphasize SDOHs’ relationship to diseases, and research concerning SDOH and empowering patient education is dispersed. Addressing SDOH in empowering patient education could be a relevant reinforcement when exploring solutions to health problems and supporting patient empowerment. Purpose: Study aimed 1) to describe which, how frequent and in which phases of the studies SDOH are reported in empowering patient education intervention studies and 2) to identify possible association between SDOH and empowerment as an outcome of the intervention. The purpose was to identify possible research gaps for future research and for developing patient education interventions. Methods: Integrative literature review. A systematic literature search was conducted on Cinahl, PubMed and Cochrane (on March 2023) with key search terms: patient education, intervention study and empowerment. Inclusion criteria were English, peer-reviewed empowering patient education intervention studies, which reported intervention for adult patients, nurses’ contribution to the intervention and empowerment as an outcome. Data analysis utilizes deductive and inductive content analysis. Methodological quality of included studies was evaluated with Mixed methods appraisal tool (MMAT). Results: Search identified 3135 studies and 33 met inclusion criteria. Most of the studies were randomized controlled trials or quasi experimental studies, published 1998–2023. “Behaviors and biological factors” and “psychosocial factors” were reported on targeting intervention, as an educational content or as an outcome more frequently than “material circumstances”. Interventions were targeted based on patients’ consumption potential, stressful living circumstances or biological factors. Content of the educational intervention and outcomes included various behavioural factors: diet, physical exercise, substance abuse, and psychosocial factors: psychosocial stressors, social support and coping styles. Few studies included material circumstances as an educational content. Associations between SDOH and empowerment as a patient education outcome were contradictory. Conclusions: Reporting different aspects of SDOH is distributed unevenly in empowering patient education intervention studies. Behaviours and psychosocial factors were reported broadly in empowering patient education interventions. The reporting of material circumstances was scarce, and a research gap regarding how material circumstances could be incorporated in empowering patient education was identified.

Tausta: Terveyden sosiaaliset määrittäjät (SDOH) ovat keskeinen osa strategisia tavoitteita. Terveyden sosiaaliset määrittäjät ovat olosuhteita, joissa ihmiset syntyvät, kasvavat, työskentelevät, elävät ja ikääntyvät, ja jotka voivat johtaa seurauksiin terveydessä ja terveyseroihin. Aiemmat tutkimukset korostavat usein SDOH:n suhdetta sairauksiin, ja tutkimus SDOH:n ja voimavaraistumista tukevan potilasohjauksen välillä on vähäistä. SDOH:n huomioiminen potilasohjauksessa voi muodostaa oleellisen lisän tarkasteltaessa terveysongelmien ratkaisuja ja voimavaraistumisen tukemista. Tarkoitus: Tutkimuksen tarkoituksena oli 1) kuvata SDOH voimavaraistumista tukevan potilasohjauksen interventiotutkimuksissa; mitä SDOH raportoidaan, kuinka usein ja missä vaiheessa tutkimusta, sekä 2) tunnistaa mahdollisia yhteyksiä SDOH:n ja voimavaraistumisen välillä. Tavoitteena oli tunnistaa aikaisemman tutkimuksen perusteella tutkimuksen tiedonaukkoja tulevia tutkimuksia ja potilasohjauksen kehittämistä varten. Menetelmät: Integroiva kirjallisuuskatsaus. Tiedonhaku toteutettiin helmikuussa 2023 Cinahl, PubMed ja Cochrane -tietokannoista päähakusanoilla potilasohjaus, interventiotutkimus ja voimavaraistuminen. Mukaanottokriteerit kohdentuivat englanninkielisiin, vertaisarvioituihin voimavaraistumista tukevan potilasohjauksen interventiotutkimuksiin, joissa oli otoksena aikuiset potilaat, raportoitu hoitotyön osuus ja voimavaraistuminen mitattuna intervention tuloksena. Tutkimusten menetelmällinen laatu arvioitiin Mixed method appraisal (MMAT) -työkalulla ja aineisto analysoitiin deduktiivisella ja induktiivisella sisällönanalyysilla. Tulokset: Haku tuotti 3135 tulosta, joista 33 tutkimusta valittiin katsaukseen. Enemmistö tutkimuksista oli satunnaistettuja kontrolloituja tai kvasikokeellisia tutkimuksia, julkaistu 1998–2023. ”Käyttäytymistä ja biologisia tekijöitä” sekä ”psykososiaaliset tekijöitä” raportoitiin interventioiden kohdentamisessa, intervention ohjauksen sisällössä tai lopputuloksena useammin kuin ”aineellisia olosuhteita”. Interventiota kohdennettiin potilaiden kulutusmahdollisuuksien, stressaavien elinolosuhteiden tai biologisten tekijöiden perusteella. Interventioiden ohjauksellinen sisältö ja lopputulokset sisälsivät useita käyttäytymiseen liittyviä tekijöitä: ruokavalion, liikunnan, päihteiden käytön, sekä psykososiaalisia tekijöitä: psykososiaalisia stressitekijöitä, sosiaalista tukea ja selviytymistyylejä. Tulokset SDOH:n yhteyksistä potilasohjauksen tuloksiin olivat ristiriitaisia. Päätelmät: Voimavaraistumista tukevan potilasohjauksen interventiotutkimuksissa SDOH:n raportointi jakautuu epätasaisesti. Käyttäytyminen ja psykososiaaliset tekijät oli raportoitu laajasti. Aineellisten olosuhteiden raportointi oli vähäistä, ja tutkimusaukko tunnistettiin; liittyen aineellisien olosuhteiden sisällyttämisestä ja sen tarpeellisuudesta voimavaraistumista tukevassa potilasohjauksessa.
Keywords: social determinants of health, empowering patient education, terveyden sosiaaliset määrittäjät, voimavaraistumista tukeva potilasohjaus